2016
DOI: 10.1038/srep34504
|View full text |Cite
|
Sign up to set email alerts
|

Dual targeting of ANGPT1 and TGFBR2 genes by miR-204 controls angiogenesis in breast cancer

Abstract: Deregulated expression of microRNAs has been associated with angiogenesis. Studying the miRNome of locally advanced breast tumors we unsuspectedly found a dramatically repression of miR-204, a small non-coding RNA with no previous involvement in tumor angiogenesis. Downregulation of miR-204 was confirmed in an independent cohort of patients and breast cancer cell lines. Gain-of-function analysis indicates that ectopic expression of miR-204 impairs cell proliferation, anchorage-independent growth, migration, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 40 publications
2
51
0
Order By: Relevance
“…Of all ncRNAs, microRNAs have been the subject of substantial studies, many of which have verified their roles in breast cancer development and progression [49-52]. Increasing evidence suggests cross-regulation between microRNAs and lncRNAs [53].…”
Section: Discussionmentioning
confidence: 99%
“…Of all ncRNAs, microRNAs have been the subject of substantial studies, many of which have verified their roles in breast cancer development and progression [49-52]. Increasing evidence suggests cross-regulation between microRNAs and lncRNAs [53].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several reports have proved that miR‐204 generally acts as a tumor suppressor in human cancer (Shi et al, ). Its expression is significantly downregulated in several cancers including gastric cancer, colorectal cancer, breast cancer, and hepatocellular carcinoma, as it inhibits cellular proliferation, migration, and invasion (Flores‐Pérez et al, ; Jiang, Wen, Zheng, Jian, & Deng, ; Sacconi et al, ; Yin et al, ). However, there have been very few reports about the role of miR‐204 on the adipocyte development.…”
Section: Introductionmentioning
confidence: 99%
“…Adipose tissue dysfunction directly and indirectly leads to dyslipidemia, hyperglycemia, and hypertension due to excessive caloric imbalance. Flores-Perez et al 26 found that miR-204 regulates tumor angiogenesis by targeting ANGPT1 and TGFBR2 in breast cancer. 23 Therefore, an in-depth understanding of fat deposition in pig adipose tissue can contribute to biomedical research.…”
Section: Discussionmentioning
confidence: 99%